2015
DOI: 10.1002/anie.201411438
|View full text |Cite
|
Sign up to set email alerts
|

A C3‐Symmetric Macrocycle‐Based, Hydrogen‐Bonded, Multiporous Hexagonal Network as a Motif of Porous Molecular Crystals

Abstract: A C3-symmetric π-conjugated macrocycle combined with an appropriate hydrogen bonding module (phenylene triangle) allowed the construction of crystalline supramolecular frameworks with a cavity volume of up to 58%. The frameworks were obtained through non-interpenetrated stacking of a hexagonal sheet possessing three kinds of pores with different sizes and shapes. The activated porous material absorbed CO2 up to 96 cm(3) g(-1) at 195 K under 1 atm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(73 citation statements)
references
References 52 publications
2
69
0
1
Order By: Relevance
“…[17,19] Similarly,planar C 6 -orC 3 -symmetric p-conjugated molecules 9-14 ( Figure 2) were capable of forming stacked isostructural H-HexNet sheets (Figure 9b); however,t he manner of stacking depended on the interlayer interactions (e.g., p-p stacking between p-conjugated cores). [20,[30][31][32] Interestingly,tripyrazole derivatives 27-29 (Figure 7 (Figure 9d). [25][26][27] Tr iptycene derivatives 16 and 17 produced isostructural HOFs, [39] and compound 17 was expected to possess an extremely large surface area with an SA (BET) value of 3599 m 2 g À1 .…”
Section: Isostructural Frameworkmentioning
confidence: 99%
“…[17,19] Similarly,planar C 6 -orC 3 -symmetric p-conjugated molecules 9-14 ( Figure 2) were capable of forming stacked isostructural H-HexNet sheets (Figure 9b); however,t he manner of stacking depended on the interlayer interactions (e.g., p-p stacking between p-conjugated cores). [20,[30][31][32] Interestingly,tripyrazole derivatives 27-29 (Figure 7 (Figure 9d). [25][26][27] Tr iptycene derivatives 16 and 17 produced isostructural HOFs, [39] and compound 17 was expected to possess an extremely large surface area with an SA (BET) value of 3599 m 2 g À1 .…”
Section: Isostructural Frameworkmentioning
confidence: 99%
“…The weak hydrogen‐bonding barely stabilizes the framework, so the potentially “porous” networks typically collapse or yield to structural transformation, once the solvent guest molecules are removed after thermal and/or vacuum activation. This is proven by a certain degree of hysteretic desorption isotherms of many H‐bonded porous materials …”
Section: Methodsmentioning
confidence: 96%
“…Crystal structures revealed that this series of molecules first constructed robust hydrogenbondedh exagonal networks (H-HexNets) with dual or triple void spaceso fs ystematically varied sizes and shape,a nd then LA-H-HexNets formed without interpenetration into the bulk crystal.W ea pplied a C 3 -symmetric p-conjugated macrocycle in carbon dioxide adsorption by combining the macrocycle with an appropriate hydrogen-bonding module (phenylene triangle (PhT)). [5] Furthermore, we also demonstrated that LA-H-HexNet could be applied asaplatform to align functional molecules such as C 60. [6] During the past two decades, the surface/interface phenomenon has attracted increasing attention because the conformation, orientation, and packing structures of nanodeviceso n solid substrates play essential roles in determiningt heir performance.…”
Section: Introductionmentioning
confidence: 81%
“…Crystal structures revealed that this series of molecules first constructed robust hydrogen‐bonded hexagonal networks (H‐HexNets) with dual or triple void spaces of systematically varied sizes and shape, and then LA‐H‐HexNets formed without interpenetration into the bulk crystal. We applied a C 3 ‐symmetric π‐conjugated macrocycle in carbon dioxide adsorption by combining the macrocycle with an appropriate hydrogen‐bonding module (phenylene triangle (PhT)) . Furthermore, we also demonstrated that LA‐H‐HexNet could be applied as a platform to align functional molecules such as C 60.…”
Section: Introductionmentioning
confidence: 99%